THE INFLUENCE OF PROFIT SHARING, TRADE FINANCING, AND THE NON PERFORMING FINANCING RATIO TO THE RETURN ON ASSET OF ISLAMIC RURAL BANKS IN CENTRAL JAVA (2013-2015 PERIOD) - Nur Hayati; Umiyati Umiyati; Ilhamdi Ilhamdi (AFEBI Islamic Finance and Economic Review, 2018)
This study examines how profit-loss sharing (PLS) and trade financing as well as non performing financing (NPF) can affect the Return on Asset (ROA ) of Islamic Rural Banks in Cental Java (Period of 2013-2015). The sample selection method used is the purposive sampling. The data analysis method used a multiple regression dated panel with a significance level of 5% (0.05). The result of the data analysis showed that the suitable model used in this study is the Common Effect Model (CEM). Simultaneous independent variables significantly influence ROA. The partial, variable of PLS has negative effect on the ROA of Islamic Rural Banks ,while trade financing dan NPF did not have a significant effect on the ROA of Islamic Rural Banks.Keywords: Non Performing Financing (NPF), Profit-Loss Sharing Financing, Return On Asset (ROA), Trade Financing